The principles of the protection of the environment from pollution production and consumption waste (Journal of actual problems of jurisprudence, 2019)
Basic principles of pollution prevention waste production and consumption are fixed in the regulations ofdifferent hierarchical levels and different departments. These principles should be presented in a separatesection of the Environmental Code of the Republic of Kazakhstan, as it is for them to be built new legislationdetailing the issues of neutralization, recycling and disposal of waste, which in the long term should serveas a benchmark when developing the necessary legal acts bylaw level.Keywords: principles, environment, waste, waste pollution.